Analysis of Micro Translation Strategies Used by the Main Character in Subtitle Conversation Movie “Guardians of the Galaxy Vol 2” - Diffa Aulia Astiningsih; Raden Arief Nugroho (Journal of English Language Teaching and Linguistics, 2024)
The aim of this research is to identify the micro-strategies and quality of translation used by the translator in the subtitle conversation of the main character in the movie “Guardians of the Galaxy Vol 2”. The data sources used are words, phrases, and sentences found in the main character's utterances. The method employed in this study's method of translation was descriptive and qualitative in character of Schjoldager et al. (2008) followed by a quality assessment of the translation by Nababan, et al. (2012) with the following steps: 1) find the data analyzed in the film; 2) classify the micro-strategies and quality; 3) find the conclusions. There are some reasons for using these micro-strategies and qualities: 1) more detailed and specific; 2) more accurate in assessing the quality of the translation. The objectives of this study are: 1) to analyze and classify the data based on the category of micro-strategies; 2) identify the quality of the translation; 3) to find out what type of translation is used most often and what is the quality of the translation as a whole. As a result, the direct translation strategy is the one that translators utilize the most frequently, which reaches 77 data with a percentage of (42.55%). This strategy makes it easier for the target language because this translation emphasizes the translation of the words, so all source language information is conveyed correctly. The researcher also found that the direct translation technique has a higher percentage of translation quality than other translation techniques. The researcher concludes that direct translation is a translation that is more efficient to use for a translation because the target language quickly understands it.